Revitalization of Maritime Local Wisdom in Improving Financial Literacy of the Pulopanjang Village Community, Puloampel District, Serang, Banten - Elly K. N., Nabila; Sari, Gema Ika (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Pulopanjang Village in Puloampel District, Serang, Banten, possesses abundant maritime resources but continues to face economic challenges due to limited financial literacy. This study explores the revitalization of maritime local wisdom as a culturally grounded approach to enhance financial literacy among fishing households and small-scale maritime business actors. The objective is to develop a model of community empowerment that harmonizes traditional values with modern financial practices. The research employed a Participatory Action Research (PAR) approach combined with community-based education, including workshops, counseling, and simulations. Quantitative data were collected through pre-test and post-test surveys to measure knowledge improvement, while qualitative insights were obtained via focus group discussions, interviews, and participatory observation. Results indicated significant improvement in participants’ budgeting, saving, and record-keeping practices. The integration of local wisdom—such as gotong royong (mutual cooperation), cooperative savings, and musyawarah kampung (village deliberation)—provided culturally resonant methods that increased comprehension and acceptance of financial literacy concepts. Additionally, adapting these practices for elementary school education through storytelling and role-playing activities proved effective in instilling early financial awareness among children. The findings confirm that revitalizing maritime local wisdom not only strengthens household economic resilience but also ensures intergenerational transfer of financial knowledge. This culturally embedded approach highlights the potential of integrating tradition into financial education programs for sustainable community empowerment in coastal areas.